The molecular epidemiology and ecology of Neisseria species in the African meningitis belt - Diallo, K (2017)
Neisseria meningitidis (Nm) is one of the major causes of bacterial meningitis in the African meningitis belt (AMB). This organism is part of the genus Neisseria, which includes ten human restricted species, mostly harmless commensals of the nasopharynx; however, Nm is capable of causing invasive meningococcal disease. The transition from carriage to pathogenic state remains perplexing, and strict virulece factors have yet to be identified. It has been hypothesised that non-pathogenic Neisseria (NPN) carried asymptomatically in the oroopharynx could play a role in modulating carriage of Nm, and therefore, its likelihood of invasion. In chapter 3, the diversity of the genus was characterised within a collection of 46 034 nasopharyngeal samples obtained across the AMB: five different species were identified, with Nm and NPNs displaying inversely related risk factors fo carriage. Chapter 5 presents the whole genome sequence (WGS) analysis of 107 Neisseria isolates unclassified by other methods. This higher genetic resolution, complemented with the use of a novel speciation approach, revealed seven novel Neisseria species, mostly collected in African countries. The invasive potential may also be due to the presence of particular genetic factors in the meningococcal genome. Chapter 4 presents the WGS comparison of 23 carried and invasive serogroup A Nm collected in Chad during the 2011 meningitis epidemic. Isolates from both phenotypic groups were found to be part of the same bacterial populations; however, discrete clusters were identified, associated with distinct age groups. These results indicate that genomic analyses are essential to appropriately study Neisseria diversity, and that lower resolution methods have greatly underestimated the diversity of the genus in Africa. The identification of Nm clusters associated with certain niches and of the differences in carriage risk factors suggests that variation in the environment, including the presence of NPNs, may be key in modulating carriage of Nm.